2018
DOI: 10.1213/ane.0000000000003430
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Perioperative Respiratory Adverse Events Among Caucasian and African American Children Undergoing General Anesthesia

Abstract: In a multivariable logistic analysis, African American pediatric patients were shown to have significantly higher odds of PRAEs when compared with the Caucasian group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
0
18
2
Order By: Relevance
“…Our data support what multiple studies have shown. Age, race/ethnicity, and ASA physical status are independent risk factors for PRAEs . Conversely, while there is literature which suggests that BMI also plays a role in PRAEs, our data did not find support this finding …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our data support what multiple studies have shown. Age, race/ethnicity, and ASA physical status are independent risk factors for PRAEs . Conversely, while there is literature which suggests that BMI also plays a role in PRAEs, our data did not find support this finding …”
Section: Discussioncontrasting
confidence: 99%
“…Age, race/ethnicity, and ASA physical status are independent risk factors for PRAEs. 5,16,17 Conversely, while there is literature which suggests that BMI also plays a role in PRAEs, our data did not find support this finding. 5,16,18 Although it did not reach statistical significance, the odds ratio (OR) associated with dexmedetomidine administration was 0.4, suggesting that it may decrease the incidence of PRAEs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The current consensus from the limited studies investigating the role of preoperative PSG in the group <2 years of age is to confirm the diagnosis of OSA prior to surgical intervention as there is a higher risk of complications in this age group 57,76‐81 . The American Academy of Otolaryngology/Head and Neck Surgery (AAO/HNS) revised tonsillectomy guidelines published in 2019 state that children with oSDB should be referred for preoperative polysomnography (PSG) if they are (a) <2 years of age or if they exhibit any of the following: (b) obesity, (c) Down syndrome, (d) craniofacial abnormalities, (e) neuromuscular disorders, (f) sickle cell disease, or (g) mucopolysaccharidoses 1 .…”
Section: Introductionmentioning
confidence: 99%